Congruence of parent and child perceptions of parental acceptance-rejection - Ekmekci, Ayşen Yıldırım. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The purpose of this study was to establish the reliability of the Parent Psychological Adjustment Questionnaire (Parent PAQ) and to explore the congruence between the parents‟ and children‟s perceptions regarding the psychological adjustment of the child. Secondly, the purpose was to explore the level of agreement (congruence) between the perceptions of parents and children on the four dimensions of the parental acceptance-rejection and perceived control, and whether the level of agreement (congruence) varied significantly in loving families versus less than loving families. The participants in the current study consisted of 185 sixth and seventh grade students and their parents. The Parental Acceptance-Rejection Questionnaire (PARQ) and the Psychological Adjustment Questionnaire (PAQ) were the measures of the study. The findings indicated that the Parent PAQ was a reliable questionnaire for the assessment of the psychological adjustment of children by their parents. Overall, the children and their parents reported more acceptance than rejection. However, the children found their mothers to be less accepting and less controlling, their fathers were more accepting and more controlling, and this differed from the parents‟ reports. Although the children perceived themselves as being psychologically welladjusted on average, they perceived themselves to be psychologically less adjusted than their parents reported. The children from the more loving families found their parents more accepting than the parents had reported, and the children from less than loving families thought their parents were less accepting. Another finding was that when the children perceived more parental rejection and control, they perceive more negative psychological adjustment.
Keywords: Parental acceptance.; Parental rejection.; Self-perception in children.; Parent and child.